Baby Genomics: Tracing the Evolutionary Changes That Gave Rise to Placentation. (13th February 2020) - Hao, Yue; Lee, Hyuk Jin; Baraboo, Michael; Burch, Katherine; Maurer, Taylor; Somarelli, Jason A; Conant, Gavin C
Abstract: It has long been challenging to uncover the molecular mechanisms behind striking morphological innovations such as mammalian pregnancy. We studied the power of a robust comparative orthology pipeline based on gene synteny to address such problems. We inferred orthology relations between human genes and genes from each of 43 other vertebrate genomes, resulting in ∼18, 000 orthologous pairs for each genome comparison. By identifying genes that first appear coincident with origin of the placental mammals, we hypothesized that we would define a subset of the genome enriched for genes that played a role in placental evolution. We thus pinpointed orthologs that appeared before and after the divergence of eutherian mammals from marsupials. Reinforcing previous work, we found instead that much of the genetic toolkit of mammalian pregnancy evolved through the repurposing of preexisting genes to new roles. These genes acquired regulatory controls for their novel roles from a group of regulatory genes, many of which did in fact originate at the appearance of the eutherians. Thus, orthologs appearing at the origin of the eutherians are enriched in functions such as transcriptional regulation by Krüppel-associated box-zinc-finger proteins, innate immune responses, keratinization, and the melanoma-associated antigen protein class. Because the cellular mechanisms of invasive placentae are similar to those of metastatic cancers, we then used our orthology inferences to explore the association between placenta invasion and cancer metastasis. Again echoing previous work, we find that genes that are phylogenetically older are more likely to be implicated in cancer development.